Facilitating the mission and vision of the Ministry Of Higher Education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
In the Ninth Malaysia Plan, the Ministry of Higher Education (MOHE) has been allocated over RM18 billion to provide better facilities and promote quality at the various universities and colleges in Malaysia